Structural and functional studies of the transcriptional regulator Seb1 in fission yeast - Wittmann, S (2016)
RNA polymerase II (Pol II) is responsible for the transcription of all protein-coding and some non-coding genes in eukaryotes. Its largest subunit, Rpb1, contains a unique C-terminal domain (CTD) which consists of repeats of the heptad YSPTSPS. It acts as a binding platform for proteins that control the different stages of transcription and their recruitment is regulated mainly by differential phosphorylation of residues contained within the CTD. Previous studies could unveil proteins containing a CTD-interacting domain (CID) as important players that specifically bind to certain phosphorylation types of the CTD. More precisely, they were shown to be important for the last step of transcription, termination. Despite extensive research over the past 30 years, the exact mechanism of how these proteins facilitate the dislodgement of Pol II from the DNA template, still remains unknown. The work presented here contains detailed studies of the CID-containing protein Seb1 from the fission yeast Schizosaccharomyces pombe, revealing an unexpectedly broad role of this protein in transcription termination. In addition to a CID, Seb1 also contains an RNA recognition motif (RRM) which allows direct binding to RNA. Here, I present high-resolution crystal structures of both domains of Seb1. While the CID has a very conserved fold, the RNA binding regions contains an unusual arrangement of a canonical RRM intertwined with a second domain that are both important for RNA binding. Structure-based mutations were introduced and a combination of in vitro and genome-wide in vivo studies uncover Seb1 as an essential player in transcription termination. Importantly, both domains are required to promote the full function of Seb1. Despite its homology to the well-studied budding yeast protein Nrd1, the role of Seb1 in fission yeast is quite different. This thesis therefore provides important insight into the mechanisms that underlie eukaryotic transcription termination.